Ozone decomposition catalyst as well as preparation method and application thereof

The preparation of manganese-based catalysts with high specific surface area and stable oxygen vacancies through inorganic salt-assisted mechanochemistry has solved the problem of easy deactivation of manganese-based catalysts in high humidity environments, achieved efficient ozone decomposition and long-term stability, and was suitable for water treatment and air purification.

CN119657117APending Publication Date: 2025-03-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411767500.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Manganese-based catalysts are prone to inactivation under high humidity environments, limiting their application potential under a wider range of environmental conditions.

Method used

An inorganic salt-assisted mechanochemistry method is used to prepare α-MnO2 or doped metal α-MnO2 catalyst. By adjusting the raw material ratio and ball milling conditions, a mesoporous catalyst with a high specific surface area, stable oxygen vacancies and hydrophobic surface is formed.

Benefits of technology

It realizes the efficient ozone decomposition ability and good stability of the catalyst, can maintain high-efficiency performance for a long time under high humidity conditions, and is suitable for water treatment and air purification fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657117A_ABST
    Figure CN119657117A_ABST
Patent Text Reader

Abstract

The invention discloses an ozone decomposition catalyst as well as a preparation method and application thereof. The ozonolysis catalyst not only has efficient ozonolysis capability, but also has good stability and reusability, can be widely applied to the fields of water treatment, air purification and the like, and effectively removes ozone pollution in the environment. The ozonolysis catalyst is prepared by using water-soluble inorganic salt as an auxiliary agent and adopting an inorganic salt-assisted mechanochemical method, the process is simple, a complex chemical synthesis process is avoided, the production cost is reduced, and the ozonolysis catalyst is suitable for large-scale industrial production; the composition and the performance of the catalyst can be accurately regulated and controlled by adjusting the raw material ratio and the ball milling condition; and the water-soluble inorganic salt is used as an auxiliary agent, so that subsequent water washing removal is facilitated, and environmental pollution and energy consumption are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an ozone decomposition catalyst, a preparation method and application thereof, and belongs to the technical field of catalyst preparation. Background Art

[0002] In recent years, with the acceleration of industrialization and the continuous advancement of urbanization, the problem of ozone pollution has become increasingly prominent and has become an important issue affecting global environmental quality and human health. Ozone (O), as a gas with extremely strong oxidizing ability, has a wide range of applications in nature and industrial production, such as deodorization, air sterilization, organic matter degradation, medical equipment disinfection and advanced water treatment. However, the excessive presence and improper emission of ozone also bring many negative effects, such as harming human health, inhibiting plant growth, acting as a greenhouse gas and photochemical pollution to further aggravate global warming or damage the atmospheric environment.

[0003] Given the serious situation and complexity of ozone pollution, exploring effective ozone removal strategies has become a core issue in the field of environmental science research. In this context, ozone catalytic decomposition removal technology has won wide attention due to its mild reaction conditions, excellent treatment efficiency, environmental friendliness and high safety. The core of this technology lies in the development of efficient and stable catalysts to promote the efficient catalytic decomposition of ozone.

[0004] Manganese-based (MnO x ) catalysts stand out among many candidate materials due to their excellent catalytic activity in ozone decomposition and have become a hot topic of research (CN111974380A, CN113559848A, CN114904514A). However, although manganese-based catalysts show good application prospects, their catalytic performance faces the challenge of significant decline in high humidity environments, that is, the problem of easy deactivation. This problem limits the application potential of manganese-based catalysts under a wider range of environmental conditions.

[0005] Therefore, the current research focus is not only to further improve the ozone decomposition efficiency of manganese-based catalysts, but also to solve their stability problems under high humidity conditions, so as to develop ozone decomposition catalysts that are suitable for more complex environmental conditions and have better performance. Through the innovation of synthetic methods, constructing catalytic materials with high specific surface area, stable oxygen vacancies, and hydrophobic surfaces is an important means to improve the performance of ozone decomposition catalysts. Summary of the invention

[0006] According to one aspect of the present application, an ozone decomposition catalyst is provided, which not only has efficient ozone decomposition ability, but also has good stability and reusability. The catalyst can be widely used in the fields of water treatment, air purification, etc., and effectively removes ozone pollution in the environment.

[0007] The ozone decomposition catalyst contains α-MnO2 or α-MnO2 doped with metal Me; the α-MnO2 or α-MnO2 doped with metal Me contains mesopores with a specific surface area of ​​150m 2 / g~300m 2 / g, the average pore size of the mesopores is 3nm to 5nm, and the pore volume is 0.1cm 3 / g~0.5cm 3 / g; the Me in the α-MnO2 doped with metal Me is selected from at least one of copper, cobalt, nickel, cerium, lanthanum and zirconium.

[0008] Preferably, the α-MnO2 or α-MnO2 doped with metal Me has a specific surface area of ​​150 m 2 / g~250m 2 / g, the average pore size of the mesopores is 4nm-5nm, and the pore volume is 0.2cm 3 / g~0.4cm 3 / g.

[0009] Further preferably, the α-MnO2 or α-MnO2 doped with metal Me has a specific surface area of ​​175.94 m 2 / g~219.08m 2 / g, the average pore size of the mesopores is 3.722nm-4.726nm, and the pore volume is 0.192cm 3 / g~0.320cm 3 / g.

[0010] Preferably, Me in the α-MnO2 doped with metal Me is Co.

[0011] According to another aspect of the present application, a method for preparing the ozone decomposition catalyst is provided. The preparation method adopts an inorganic salt-assisted mechanochemical method, has a simple process, avoids a complex chemical synthesis process, reduces production costs, and is suitable for large-scale industrial production; by adjusting the raw material ratio and ball milling conditions, the catalyst composition and performance can be precisely controlled; using a water-soluble inorganic salt as an auxiliary agent, it is easy to remove by subsequent water washing, reducing environmental pollution and energy consumption.

[0012] The preparation method of the ozone decomposition catalyst comprises: using a water-soluble inorganic salt as an auxiliary agent, and using a mechanochemical method to prepare a raw material containing a manganese salt to obtain the ozone decomposition catalyst;

[0013] The water-soluble inorganic salt is selected from sodium salt and / or potassium salt.

[0014] The manganese salts are potassium permanganate and divalent manganese salts.

[0015] Preferably, the method for preparing the ozone decomposition catalyst comprises the following steps:

[0016] (1) mixing the raw material containing manganese salt with the water-soluble inorganic salt;

[0017] (2) placing the mixture obtained in step (1) in a ball mill for ball milling;

[0018] (3) The material after ball milling in step (2) is washed with water to remove water-soluble inorganic salts, and then dried to obtain the ozone decomposition catalyst.

[0019] Preferably, the water-soluble inorganic salt is selected from at least one of sodium chloride, potassium chloride, potassium bromide, sodium bicarbonate and sodium sulfate.

[0020] The water-soluble inorganic salt is used to promote the mechanochemical reaction and is removed in the subsequent water washing process.

[0021] Preferably, the divalent manganese salt is selected from at least one of manganese chloride, manganese carbonate, manganese nitrate, manganese acetate and manganese oxalate.

[0022] Preferably, the raw material containing manganese salt also includes a precursor.

[0023] The precursor is used to adjust the composition and performance of the catalyst.

[0024] Preferably, the precursor is selected from at least one of nitrates, chlorides, carbonates and oxalates of copper, cobalt, nickel, cerium, lanthanum and zirconium.

[0025] Preferably, in the raw material containing manganese salt, the molar ratio of the manganese salt to the precursor is the manganese salt: the precursor=1000-2:1.

[0026] Preferably, the mass ratio of the raw material containing manganese salt to the water-soluble inorganic salt is

[0027] The raw material containing manganese salt: the water-soluble inorganic salt = 1:10-3000.

[0028] That is, the molar ratio of the manganese salt to the precursor is controlled within the range of 1000 / 1 to 2 / 1, and the total mass of the raw material containing the manganese salt accounts for 1 / 10 to 1 / 3000 of the water-soluble inorganic salt, so as to ensure the rationality of the composition and stability of the catalyst.

[0029] After the raw materials are mixed according to the proportion, they are ball-milled in a high-energy ball mill.

[0030] Preferably, the processing conditions of the ball milling treatment include: medium filling rate of 10-40%, ball milling time of 10-120min, and ball milling speed of 1000-5000r / min.

[0031] Optionally, the medium material used in the ball milling process is any one of zirconium oxide, stainless steel or agate.

[0032] Through high-energy ball milling, chemical reactions and physical mixing between raw materials are promoted to form a uniform mixture.

[0033] The ball-milled mixture is washed with water to remove water-soluble inorganic salts to obtain a pure catalyst precursor. It is then dried, preferably at a temperature of 80 to 300° C. and for 5 to 20 hours, to ensure that the moisture in the catalyst is fully removed while maintaining the structural stability of the catalyst.

[0034] According to another aspect of the present application, the use of the ozone decomposition catalyst in catalytic ozone decomposition is provided. The ozone decomposition catalyst can be widely used in fields such as water treatment and air purification to effectively remove ozone pollution in the environment.

[0035] The beneficial effects of this application include but are not limited to:

[0036] (1) Excellent performance: The ozone decomposition catalyst provided in the present application has efficient ozone decomposition ability and good stability.

[0037] (2) Simple process: The present invention adopts an inorganic salt-assisted mechanochemical method, which avoids the complicated chemical synthesis process and reduces the production cost.

[0038] (3) Controllability: By adjusting the raw material ratio and ball milling conditions, the catalyst composition and performance can be precisely controlled.

[0039] (4) Environmental protection and energy saving: Using water-soluble inorganic salts as auxiliary agents facilitates subsequent water washing and removal, reducing environmental pollution and energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the SEM image of sample 1# prepared in Example 1.

[0041] Figure 2 This is the XRD diagram of sample 1# prepared in Example 1.

[0042] Figure 3 This is a BET comparison chart of sample 1# prepared in Example 1 and sample D1# prepared in Comparative Example 1.

[0043] Figure 4 This is a comparison chart of the activities of sample 1# prepared in Example 1 and sample D1# prepared in Comparative Example 1.

[0044] Figure 5This is a long-term stability test chart of sample 1# prepared in Example 1 for catalytic ozone decomposition under humid conditions.

[0045] Figure 6 This is a long-term stability test chart of the synergistic degradation of sample 1# prepared in Example 1 and volatile organic matter VOC (toluene).

[0046] Figure 7 It is a performance comparison chart of sample 1# prepared in Example 1 and sample 6# prepared in Example 6 under low temperature and high humidity conditions. DETAILED DESCRIPTION

[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0048] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0049] In the embodiment, the ball mill adopts a TJX-450 planetary ball mill produced by Dongfang Tianjing.

[0050] SEM morphology analysis was performed using a JEOL JSM-7800F scanning electron microscope.

[0051] X-ray diffraction (XRD) was performed using a PANAlytical X'pert Pro-1 powder X-ray diffractometer using Cu Kα radiation in a scanning range of 10° to 90°.

[0052] The pore volume and specific surface area were analyzed by BET physical adsorption using Quantachrome NOVA-2200E specific surface area tester.

[0053] Example 1 Preparation of Sample 1#

[0054] Weigh 1g potassium permanganate, 1.87g manganese (II) chloride tetrahydrate and 10g sodium chloride, add to 50mL agate ball mill and mix evenly, set the ball mill speed to 2000rpm, and the ball milling time is 90min. After ball milling, add 100mL of deionized water to the tank, ultrasonically dissolve the inorganic salt and unreacted precursor, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 110℃ for 12h to obtain the ozone decomposition catalyst, which is recorded as sample 1#.

[0055] Example 2 Preparation of Sample 2#

[0056] Weigh 1g potassium permanganate, 2.38g manganese nitrate (II) tetrahydrate and 20g sodium chloride, add to 50mL zirconium oxide ball mill and mix evenly, set the ball mill speed to 1000rpm, and the ball milling time is 120min. After ball milling, add 100mL deionized water to the tank, ultrasonically dissolve the inorganic salt and unreacted precursor, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 80℃ for 20h to obtain the ozone decomposition catalyst, which is recorded as sample 2#.

[0057] Example 3 Preparation of Sample 3#

[0058] Weigh 2g potassium permanganate, 3.74g manganese (II) chloride tetrahydrate, 1.06g copper chloride and 15g sodium chloride, add to 50mL zirconium oxide ball mill and mix evenly, set the ball mill speed to 2500rpm, and the ball milling time is 60min. After ball milling, add 200mL deionized water to the tank, ultrasonically dissolve the inorganic salt and unreacted precursor, filter and separate the solid powder, and wash the product repeatedly with deionized water. Finally, dry at 200℃ for 8h to obtain the ozone decomposition catalyst, which is recorded as sample 3#.

[0059] Example 4 Preparation of Sample 4#

[0060] Weigh 2g potassium permanganate, 3.52g manganese acetate (II), 0.53g copper chloride, 5.15g cerium nitrate hexahydrate and 20g sodium chloride, add to 50mL zirconium oxide ball mill and mix evenly, set the ball mill speed to 2000rpm, and the ball milling time is 80min. After ball milling, add 200mL deionized water to the tank, ultrasonically dissolve the inorganic salt and unreacted precursor, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 150℃ for 12h to obtain the ozone decomposition catalyst, which is recorded as sample 4#.

[0061] Example 5 Preparation of Sample 5#

[0062] Weigh 1g potassium permanganate, 1.87g manganese chloride tetrahydrate, 1.15g nickel nitrate hexahydrate and 15g sodium chloride, add to 50mL agate ball mill and mix evenly, set the ball mill speed to 1500rpm, and the ball milling time is 120min. After ball milling, add 100mL of deionized water to the tank, ultrasonically dissolve the inorganic salts and unreacted precursors, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 100℃ for 8h to obtain an ozone decomposition catalyst, recorded as sample 5#.

[0063] Example 6 Preparation of Sample 6#

[0064] Weigh 1g potassium permanganate, 1.87g manganese chloride tetrahydrate, 2.30g cobalt nitrate hexahydrate and 5g sodium chloride, add to 50mL stainless steel ball mill and mix evenly, set the ball mill speed to 1500rpm, and the ball milling time is 120min. After ball milling, add 100mL of deionized water to the tank, ultrasonically dissolve the inorganic salts and unreacted precursors, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 100℃ for 8h to obtain an ozone decomposition catalyst, recorded as sample 6#.

[0065] Example 7 Preparation of Sample 7#

[0066] Weigh 1g potassium permanganate, 1.87g manganese chloride tetrahydrate, 0.57g nickel nitrate hexahydrate, 1.43g copper nitrate trihydrate and 15g sodium chloride, add to 50mL agate ball mill and mix evenly, set the ball mill speed to 1200rpm, and the ball milling time is 100min. After ball milling, add 100mL of deionized water to the tank, ultrasonically dissolve the inorganic salts and unreacted precursors, filter and separate the solid powder, and repeatedly wash the product with deionized water. Finally, dry at 100℃ for 8h to obtain an ozone decomposition catalyst, recorded as sample 7#.

[0067] Example 8 SEM and XRD Characterization of Samples 1# to 7#

[0068] The morphology of samples 1# to 7# was characterized by scanning electron microscopy, and a typical example is the SEM photo of sample 1#. Figure 1 As shown in the figure, it can be seen that sample 1# contains both small particles of several microns and large particles of about 10 microns, and a rough mesoporous structure can be clearly observed on the surface of the large particles. The morphology of samples 2# to 7# is similar to that of sample 1#.

[0069] X-ray powder diffraction was used to characterize the phases of samples 1# to 7#. A typical example is the XRD spectrum of sample 1#. Figure 2 As shown in the figure, it can be seen that sample 1# is mainly α-phase MnO2 crystals, with a wide diffraction peak and a low degree of crystallinity, indicating that the sample also contains a large amount of amorphous structure. The XRD patterns of samples 2#-7# are similar to those of sample 1#, that is, the peak positions are the same, but the peak intensities are slightly different.

[0070] Comparative Example 1 Preparation of Sample D1#

[0071] Weigh 1g potassium permanganate and 1.87g manganese (II) chloride tetrahydrate, add them into a 50mL agate ball mill and mix them evenly. Set the ball mill speed to 2000rpm and the ball milling time to 90min. After ball milling, add 100mL of deionized water to the tank, ultrasonically dissolve the unreacted precursor, filter and separate the solid powder, and wash the product repeatedly with deionized water. Finally, dry at 110℃ for 12h to obtain an ozone decomposition catalyst, which is recorded as sample D1#.

[0072] Example 9 Physical adsorption results of samples 1#-7# and sample D1#

[0073] Physical adsorption was used to characterize samples 1# to 7# and D1#. The results showed that the specific surface areas of samples 1# to 7# were between 150m 2 / g~300m 2 / g, all contain mesopores; the average pore size of the mesopores is distributed between 3 and 5 nm, and the pore volume is distributed between 0.1 cm 3 / g~0.5cm 3 / g.

[0074] Sample 1# and sample 2# are typical representatives. The BET characterization result of sample 1# is: the specific surface area is 219.08m 2 / g, pore diameter is 4.726nm, pore volume is 0.320cm 3 / g.

[0075] The BET result of sample 2# is a specific surface area of ​​175.94 m 2 / g, pore diameter is 3.722nm, pore volume is 0.192cm 3 / g.

[0076] The BET comparison chart of sample 1# and sample D1# is shown in Figure 3 ,It can be seen from the figure that both samples are mesoporous materials with pore diameters between 2-50nm, but sample 1 has a larger specific surface area, larger pore diameter, and larger pore volume.

[0077] Example 10 Performance Test of Samples 1# to 7# and Sample D1# as Ozone Decomposition Catalysts

[0078] Sample 1# and comparative sample D1# were tested for ozone decomposition performance in a fixed bed reactor. The gas composition was air containing 40 ppm ozone concentration and the mass space velocity was 300,000 mL g -1 h -1 , reaction temperature 30℃, relative humidity RH=50%. Figure 4It can be seen that under the above conditions, the ozone conversion rate of the sample of Example 1 under dry gas conditions reached 100%, the conversion rate under wet gas conditions was stable at 85%, and the ozone conversion rate was still able to stabilize at 100% after switching back to dry gas conditions. Although the initial conversion rate of the comparative sample D1# under dry gas conditions was also 100%, it dropped to 99% after 6 hours, and the stable conversion rate was only 77% after switching to wet gas. After switching back to dry gas, the ozone removal rate further dropped, and dropped to 98% after 6 hours. Compared with the comparative sample D1#, sample 1# has obvious advantages in both dry gas stability and conversion rate under wet gas.

[0079] Figure 5 The long-term stability of ozone decomposition of sample 1 under high humidity and high air velocity conditions is shown. The reaction conditions are air velocity 330000mLg -1 h -1 , ozone concentration 3ppm, water content 4%, temperature 130°C. Sample 1# maintained 100% ozone removal rate at 1000 hours.

[0080] Figure 6 The long-term stability of ozone decomposition of sample 1# under high humidity, high air velocity and VOC toluene is shown. The reaction conditions are air velocity 330000mLg -1 h -1 , ozone concentration 3.5ppm, water content 4%, toluene content 10ppm, temperature 186°C. Sample 1# maintained 100% ozone removal rate at 1000 hours.

[0081] The results of samples 2# to 7# are similar to those of sample 1#. They also show the long-term stability of ozone decomposition under high humidity, high air velocity and the presence of VOC toluene. The reaction conditions are air velocity 330000mLg -1 h -1 , ozone concentration 3.5ppm, water content 4%, toluene content 10ppm, temperature 186℃, samples 2# to 7# maintained 100% ozone removal rate for 1000 hours.

[0082] Figure 7 The sample #6 doped with Co showed better low-temperature activity and water poisoning resistance than the undoped sample #1 at near room temperature and high humidity.

[0083] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An ozone decomposition catalyst, characterized in that Containing α-MnO2 or α-MnO2 doped with metal Me; the α-MnO2 or α-MnO2 doped with metal Me contains mesopores: The specific surface area is 150m 2 / g~300m 2 / g, the average pore size of the mesopores is 3nm to 5nm, and the pore volume is 0.1cm 3 / g~0.5cm 3 / g; The Me in the α-MnO2 doped with metal Me is selected from at least one of copper, cobalt, nickel, cerium, lanthanum and zirconium; Preferably, in the α-MnO2 or α-MnO2 doped with metal Me: The specific surface area is 150m 2 / g~250m 2 / g, the average pore size of the mesopores is 4nm-5nm, and the pore volume is 0.2cm 3 / g~0.4cm 3 / g.

2. The method for preparing the ozone decomposition catalyst according to claim 1, characterized in that: The ozone decomposition catalyst is prepared by a mechanochemical method using a raw material containing a manganese salt and using a water-soluble inorganic salt as an auxiliary agent; The water-soluble inorganic salt is selected from sodium salt and / or potassium salt; The manganese salts are potassium permanganate and divalent manganese salts.

3. The preparation method according to claim 2, characterized in that: The following steps are involved: (1) mixing the raw material containing manganese salt with the water-soluble inorganic salt; (2) placing the mixture obtained in step (1) in a ball mill for ball milling; (3) The material after ball milling in step (2) is washed with water to remove water-soluble inorganic salts, and then dried to obtain the ozone decomposition catalyst.

4. The preparation method according to claim 2, characterized in that: The water-soluble inorganic salt is selected from at least one of sodium chloride, potassium chloride, potassium bromide, sodium bicarbonate and sodium sulfate; The divalent manganese salt is selected from at least one of manganese chloride, manganese carbonate, manganese nitrate, manganese acetate and manganese oxalate.

5. The preparation method according to claim 4, characterized in that: The raw material containing manganese salt also includes a precursor; the precursor is selected from at least one of nitrates, chlorides, carbonates and oxalates of copper, cobalt, nickel, cerium, lanthanum and zirconium.

6. The preparation method according to claim 4, characterized in that: In the raw material containing manganese salt, the molar ratio of the manganese salt to the precursor is The manganese salt: the precursor = 1000-2:

1.

7. The preparation method according to claim 2, characterized in that: The mass ratio of the raw material containing manganese salt to the water-soluble inorganic salt is The raw material containing manganese salt: the water-soluble inorganic salt = 1:10-3000.

8. The preparation method according to claim 2, characterized in that: The processing conditions of the ball milling treatment include: a medium filling rate of 10-40%, a ball milling time of 10-120 minutes, and a ball milling speed of 1000-5000 r / min.

9. The preparation method according to claim 2, characterized in that: The drying conditions include: a drying temperature of 80-300° C. and a drying time of 5-20 hours.

10. Use of the ozone decomposition catalyst according to claim 1 in catalytic ozone decomposition.

Citation Information

Patent Citations

  • Ozonolysis catalyst and preparation method thereof

    CN111974380A

  • High-activity ozonolysis manganese-based catalyst and preparation method thereof

    CN113559848A

  • Ozone decomposition catalyst as well as preparation method and application thereof

    CN114904514A